Evaluation of the ratcheting behavior of Cr-Mo steel used in CNG tank - Karim Aliakbari; Shahab Kamel Abbasnia; Mahmoud Shariati (Results in Engineering)
Compressed natural gas (CNG) tanks, due to the frequent filling and emptying during their service life, are constantly subjected to fatigue loading on the tank's wall, which causes premature failure. In this paper, the ratcheting behavior of 25CrMo4 steel used in constructing of a CNG tank was investigated numerically. Therefore, a series of experiments were performed to confirm the type of steel grade and the evaluation of mechanical properties. Also, ratcheting behavior is simulated numerically by the finite element method based on the nonlinear kinematic/isotropic hardening model. The novelty of this research is that the hardening coefficients of 25CrMo4 steel were estimated by particular innovative mathematical equations. The effect of amplitude stress and mean stress on the ratcheting behavior of 25CrMo4 steel was investigated numerically. Therefore, concluded that the increase of mean stress or amplitude stress effects on accumulation of ratcheting strain. Finally, to perform a validation procedure, the finite element results were compared with experimental data obtained from fatigue tests according to ASTM E606 standard and other research. Finaly concluded that the finite element simulation results were in satisfying agreement with the experimental data.